Macrophage Lysophosphatidylcholine Acyltransferase 3 Deficiency-Mediated Inflammation Is Not Sufficient to Induce Atherosclerosis in a Mouse Model - Jiang, Hui; Li, Zhiqiang; Huan, Chongmin; Jiang, Xian-Cheng (Frontiers in Cardiovascular Medicine, 2019)
Phosphatidylcholines (PCs) are structural constituents of cell membranes. The activity of acyltransferase (lysophosphatidylcholine acyltransferase [LPCAT]) is required for addition of polyunsaturated fatty acids to the sn-2 position of PCs, which are remodeled after de novo synthesis, and is therefore required to maintain cell membrane structure and function. LPCAT3 is expressed in macrophages, however, its role in mediating inflammation is still not understood, since contradictory results were reported previously. The order of LPCAT mRNA levels in mouse macrophages is as follows: LPCAT3 > LPCAT1 (60% of LPCAT3) > LPCAT2 (12% of LPCAT3) >> LPCAT4. To investigate the role of LPCAT3 in macrophages, we prepared myeloid cell-specific Lpcat3 knockout (KO) mice and found that LPCAT3 deficiency in macrophage significantly reduced certain polyunsaturated phosphatidylcholines, such as 16:0/20:4, 18:1/18:2, 18:0/20:4, and 18:1/20:4, in the plasma membrane. The ablation of LPCAT3 in macrophages significantly impact macrophage polarization, reflected by increase of M1 cells. Moreover, Lpcat3 deficiency also significantly increased Toll like 4 protein and phosphorylated c-Src in membrane lipid rafts, and increased LPS-induced IL-6 and TNFa releasing through activation of MAP kinases and NFkB. However, macrophage deletion of Lpcat3 in (LDL receptor) Ldlr KO mice, both male and female, on a Western type diet, did not have a significant impact on atherogenesis. In conclusion, LPCAT3 is one of LPCATs in macrophages, involved in PC remodeling. LPCAT3 deficiency promotes macrophage inflammatory response, however, such an effect has a marginal influence on the development of atherosclerosis.